Potencial antitrombótico de hidrolisado ácido de polissacarídeos sulfatados de Hypnea musciformis (Wulfen) J.V. Lamouroux - Peixoto, Caroline Landim (2020)
Venous thrombosis is the main cause of current morbidity and mortality. It is estimated that 2 / 1,000 individuals suffer from this disease. Antithrombotic drugs are commonly used as a prophylactic measure by those who are predisposed to thrombus formation. The most wellknown and used antithrombotics are Unfractionated Heparin (UFH) and Low Molecular Weight Heparin (LMWH), the second being obtained by depolymerizing the first. Because these drugs are produced in animals and have serious side effects such as hemorrhage, there is a demand for the discovery of new antithrombotic drugs of non-animal origin and with reduced side effects. It is known in the literature that sulfated polysaccharides from red marine algae have antithrombotic activity. This work aimed to evaluate the antithrombotic potential of the acid hydrolysis product of sulfated polysaccharides extracted from the red seaweed Hypnea musciformis (Wulfen) J.V. Lamouroux. A hydrolysis design was carried out to obtain sulfated galactans of different molecular weights. The molecular weight of the hydrolyzate was estimated by Gel Permeation Chromatography (GPC) and characterized by the presence of sulfation and functional groups characteristic by Infrared. Four samples of different molecular weights were selected to investigate their antithrombotic activity, the EX 1, 5 and 7 and the intact polysaccharide (PS-Hm). The in vitro antithrombotic activity was analyzed by the tests of partially activated thromboplastin time (APTT) and prothrombin time (TP), both using LMWH CLEXANE ® as a positive control. Only the intact PS-Hm and the EX 5 prolonged the clotting time in the APTT, and none of the analyzed samples influenced the TP. The bleeding time test was performed to assess the bleeding tendency with intact PS-Hm and EX 5, using LMWH CLEXANE ® as a positive control. The analyzed samples had no significant difference in relation to the negative control and both samples showed a hemorrhagic tendency much lower than the positive control. The results indicate that the antithrombotic and anticoagulant activity is related to the molecular weight of the sulfated polysaccharide, and that the reduction in molecular weight can reduce the hemorrhagic tendency. Such results suggest that the samples are candidates for new antithrombotic drugs, however more tests are needed to confirm the activity, such as the model of venous thrombosis in rats.